I'm Neither Racist nor Xenophobic, but: Dissecting European Attitudes towards a Ban on Muslims' Immigration - Abdeslam Marfouk (Global Labor Organization (GLO), 2018)
During his presidential campaign, the new elected President of U.S., Donald Trump, called for a complete ban on Muslims from entering the United States. Although numerous European observers have been shocked by his racist proposal, using the most recent round of the European Social Survey, this paper found that a sizeable proportion of Europeans support a similar ban in their own countries, e.g. Czech Republic (54%), Hungary (51%), Estonia (42%), Poland (33%), and Portugal (33%). The paper also provides evidence that racism and immigration phobia play a key role in shaping Europeans' support of a ban on Muslim immigration. This finding challenges the discourse and campaigns of the populist groups who exploit the `Islamization of Europe' rhetoric successfully and use various pretexts to justify a call for a ban on Muslims' immigration, e.g. the threat to security, secularism, democracy, Western `identity', culture and values.
Keywords: F22; J71; J79; 330; Internatonal migration; discrimination; islamophobia; racism; public opinion